2017
DOI: 10.1007/s00244-017-0423-8
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) and Hopanes in Plastic Resin Pellets as Markers of Oil Pollution via International Pellet Watch Monitoring

Abstract: Oil pollution in the marine environment is an unavoidable problem due to chronic input from local sources, particularly in urban areas and oil spills. Oil pollution not only causes immediate physical damages to surrounding wildlife but also some components, including higher molecular weight PAHs, can persist in the environment for many years and pose insidious threats to the ecosystem. Long-term and nontargeted monitoring of oil pollution is important. This paper examines the ability of International Pellet Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…However, Southeast Asia, Oceania, South America and Africa (except for site with history of oil spillage or experiences petroleum-related activities) recorded low concentrations. For example, plastic pellets collected from Chemu Lagoon Beach located close to Tema oil refinery in Ghana was highly polluted with 2751 ng/g-pellet [193], thus confirming the influence of crude oil pollution in increasing levels of PAHs loaded on the surface of microplastics.…”
Section: Polyaromatic Hydrocarbon (Pahs)mentioning
confidence: 75%
See 3 more Smart Citations
“…However, Southeast Asia, Oceania, South America and Africa (except for site with history of oil spillage or experiences petroleum-related activities) recorded low concentrations. For example, plastic pellets collected from Chemu Lagoon Beach located close to Tema oil refinery in Ghana was highly polluted with 2751 ng/g-pellet [193], thus confirming the influence of crude oil pollution in increasing levels of PAHs loaded on the surface of microplastics.…”
Section: Polyaromatic Hydrocarbon (Pahs)mentioning
confidence: 75%
“…Mizukawa et al [113] reported PAH concentration variations of up to 2 orders of magnitude between individual countries within a region. More recently, [193] following IPW monitoring study reported that Europe at Sao Torpes Beach, Sines in Portugal (24,400 ng/g-pellet) and Forth Estuary in UK (164,900 ng/g-pellet) were highest in concentrations of total PAHs on plastic pellets collected from 75 locations in 26 countries. The authors attributed these high concentrations to crude oil pollution.…”
Section: Polyaromatic Hydrocarbon (Pahs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported their presence on microplastics at varying concentrations of which; fluoranthene (Fluo), phenanthrene (Phe), anthracene (Anth), 3methylphenanthrene (3-MP), 9-methylphenanthrene (9-MP), 2-methylphenanthrene (2-MP), Karapanagioti et. al., 2009;Saha et al 2009;Yeo et. al., 2017).…”
Section: Poly Aromatic Hydrocarbon (Pahs)mentioning
confidence: 99%